Solid-state 13C-NMR spectroscopic determination of side-chain mobilities in zirconium-based metal–organic frameworks - G. Hempel; R. Kurz; S. Paasch; K. Saalwächter; E. Brunner (Magnetic Resonance, 2024)
Porous interpenetrated zirconium–organic frameworks (PIZOFs) are a class of Zr-based metal–organic frameworks (MOFs) which are composed of long, rod-like dicarboxylate linkers and Zr6O4(OH)4(O2C)12 nodes. Long oligoethylene glycol or aliphatic side chains are covalently attached to the linker molecules in the cases of PIZOF-10 and PIZOF-11, respectively. These side chains are supposedly highly mobile, thus mimicking a solvent environment. It is anticipated that such MOFs could be used as a solid catalyst – the MOF – with pore systems showing properties similar to a liquid reaction medium. To quantify the side-chain mobility, here we have applied different 1D and 2D NMR solid-state spectroscopic techniques like cross-polarization (CP) and dipolar-coupling chemical-shift correlation (DIPSHIFT) studies. The rather high 1H-13C CP efficiency observed for the CH2 groups of the side chains indicates that the long side chains are unexpectedly immobile or at least that their motions are strongly anisotropic. More detailed information about the mobility of the side chains was then obtained from DIPSHIFT experiments. Analytical expressions for elaborate data analysis are derived. These expressions are used to correlate order parameters and to slow motional rates with signals in indirect spectral dimensions, thus enabling the quantification of order parameters for the CH2 groups. The ends of the chains are rather mobile, whereas the carbon atoms close to the linker are more spatially restricted in mobility.